Extracted Triterpenes from Antrodia cinnamomea Reduce the Inflammation to Promote the Wound Healing via the STZ Inducing Hyperglycemia-Diabetes Mice Model - Wu, Yu-Sheng; Chen, Shiu-Nan (Frontiers in Pharmacology, 2016)
This research evaluated the effects of triterpenes on the regulation of STZ-induced hyperglycaemic diabetes through an anti-inflammatory response. Diabetic mice were orally administered various concentrations of triterpenes on a daily basis. Weight gain, volume of drinking water, and liver and spleen weight were recorded and evaluated. These evaluations presented a positive regulation to the abnormal metabolism appearance compared to the diabetic mice. In the diabetic mice, the detection of adiponectin production or elevated levels of inflammatory factors such as CCL1 and TPO expression were found to reduce hyperglycaemia and thereby induce an inflammatory response. Moreover, to the best of our knowledge, hyperglycaemia impairs the tissue healing associated with an increased and prolonged inflammatory response. An investigation of the anti-inflammatory response in wound healing as affected by the triterpenes verified the promotion of wound recovery.